1989
DOI: 10.1111/j.1550-7408.1989.tb05839.x
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Pneumocystis Fatty Acids

Abstract: The major ester‐linked fatly acids of the total lipids extracted from Pneumocystis carinii isolated from the lungs of corticosteroid‐trealed rats were 16:0, 18:0, 18:1,18:2 and 20:4. Others detected included 14:0,16:1 and 22:4. The major sphingolipid fatty acids were 16:0, 18:0,22:0,24:0 and 24:1; others included 14:0,18:1, 20:0, 23:0, 24:2 and 26:0. The total lipid fatty acid compositions of preparations from appropriate lung controls were similar to those of the organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
24
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 9 publications
4
24
0
Order By: Relevance
“…Results from the present study are in general agreement with those from previous studies from other laboratories (19,21,26). Our analyses showed that the major lipids in P. carinii include phosphatidylcholine, phosphatidylethanolamine (26), and cholesterol (19).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Results from the present study are in general agreement with those from previous studies from other laboratories (19,21,26). Our analyses showed that the major lipids in P. carinii include phosphatidylcholine, phosphatidylethanolamine (26), and cholesterol (19).…”
Section: Resultssupporting
confidence: 93%
“…Our analyses showed that the major lipids in P. carinii include phosphatidylcholine, phosphatidylethanolamine (26), and cholesterol (19). We found no evidence for the presence of either phosphonolipids or DGTS (data not shown).…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations